Method for manufacturing aluminum alloy plate for can lid

By controlling the element content and process flow during the manufacturing process of aluminum alloy plates, the problem of insufficient compressive resistance and toughness of aluminum alloy plates for tank lids is solved, efficient waste mixing and low energy consumption production are achieved, and regeneration rate and environmental protection performance are improved.

CN119895070APending Publication Date: 2025-04-25UACJ CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202480004049.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-17
Filing Date
2024-04-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the compressive resistance and toughness of the aluminum alloy plate for tank lids are insufficient, especially in the application of positive pressure tanks, which can easily lead to an increase in the risk of content leakage. At the same time, due to component limitations, it is difficult to effectively mix the tank waste, resulting in a low regeneration rate.

Method used

By controlling the content range of specific elements in the ingot and not performing intermediate heat treatment after hot rolling, the aluminum alloy plate is manufactured during the cold rolling process, and a high strength and high toughness aluminum alloy plate for can cover is achieved.

Benefits of technology

The compressive resistance and toughness of the tank lid without increasing the plate thickness is achieved, the utilization rate of new matrix metals and carbon dioxide emissions are reduced, and the tank waste can be effectively mixed and the regeneration rate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895070A_ABST
    Figure CN119895070A_ABST
Patent Text Reader

Abstract

One aspect of the present disclosure provides a method for manufacturing an aluminum alloy plate for a can lid, the method comprising a step for casting a cast ingot, a step for homogenizing the cast ingot, and a step for rolling the cast ingot, the cast ingot having a silicon (Si) content of 0.20-0.47 mass%, an iron (Fe) content of 0.30-0.59 mass%, and the balance being aluminum and unavoidable impurities. The content of copper (Cu) is from 0.11% by mass to 0.40% by mass (inclusive), the content of manganese (Mn) is from 0.70% by mass to 0.98% by mass (inclusive), and the content of magnesium (Mg) is from 1.3% by mass to 3.7% by mass (inclusive). In the rolling step, the ingot is hot-rolled and then cold-rolled without heat treatment.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This international application claims the priority of Japanese Patent Application No. 2023-067151 filed in the Japan Patent Office on April 17, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to a method for manufacturing an aluminum alloy sheet for a can cover. Background Art

[0004] In recent years, with the increasing awareness of environmental protection, aluminum alloy plates with less carbon dioxide emissions during the manufacturing process are required. The amount of new aluminum matrix metal mixed in the casting process has a significant indirect impact on carbon dioxide emissions in the aluminum manufacturing process.

[0005] The manufacture of new aluminum matrix metal consumes a lot of electricity in the refining process, resulting in a large amount of carbon dioxide emissions. Therefore, reducing the amount of new aluminum matrix metal mixed and increasing the same-grade recycling rate will help reduce carbon dioxide emissions in aluminum alloy sheet manufacturing.

[0006] Generally speaking, the amount of carbon dioxide emitted when aluminum scrap is remelted and cast can be reduced to about one-thirtieth of that when new aluminum matrix metal is manufactured. In particular, the production of aluminum alloy sheets for beverage cans used worldwide is extremely large, and further improving the same-grade recycling rate is of great significance for reducing the environmental burden.

[0007] Among them, the upper limits of the component specifications of silicon (Si), iron (Fe), copper (Cu), manganese (Mn), etc. in the can lid made of 5182 aluminum alloy (AA5182 alloy) are lower than those in the can body made of 3104 aluminum alloy (AA3104 alloy), so it is difficult to mix the scrap derived from the can material containing 3104 aluminum alloy.

[0008] For example, if the can waste (UBC: Used Beverage Can) generated on the market is mixed as it is, based on the weight ratio of the can body and the can lid, it will contain more 3104 aluminum alloy components, and therefore will easily exceed the upper limit of the composition of 5182 aluminum alloy, requiring the use of new base metal to dilute the composition.

[0009] Therefore, compared with the aluminum alloy sheet for the can body, the aluminum alloy sheet for the can cover needs to use more new base metal to adjust the composition to the composition of the 5182 aluminum alloy, resulting in a lower recycling rate. Therefore, by changing the can cover to an alloy whose composition is easily mixed with the 3104 aluminum alloy, the use rate of new base metal in the can cover can be significantly reduced.

[0010] Patent Documents 1 to 5 disclose aluminum alloy sheets for can covers, which have a composition relatively close to that of 3104 aluminum alloy and have excellent recyclability.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2001-73106.

[0014] Patent document 2: Japanese Patent Application Laid-Open No. 9-070925.

[0015] Patent document 3: Japanese Patent Application Laid-Open No. 11-269594.

[0016] Patent document 4: Japanese Patent Application Publication No. 2000-160273.

[0017] Patent document 5: Japanese Patent Application Publication No. 2016-160511. Summary of the invention

[0018] Problem that the invention aims to solve

[0019] When aluminum alloys with a composition close to that of 3104 aluminum alloy are used as alloys for can lids, the can lid's pressure resistance and material toughness decrease. The can lid's pressure resistance refers to the internal pressure value relative to the internal pressure of the can when the can lid bulges, and is the resistance value when the internal pressure of the can unexpectedly increases due to changes in the external environment.

[0020] In particular, positive pressure tanks for beer and carbonated beverages are required to have high pressure resistance. Generally speaking, the higher the strength of the material and the thicker the plate, the higher the pressure resistance. Therefore, the lid of the positive pressure tank adopts the high-strength 5182 aluminum alloy containing a large amount of magnesium (Mg).

[0021] In this regard, if the conventional 3104 aluminum alloy is used for can lids, the pressure resistance is greatly reduced, and when the internal pressure of the can unexpectedly increases, the can lid bulges and the risk of leakage of the contents increases. In addition, if the plate thickness is too thick to increase the pressure resistance, the weight of the lid increases and the cost of the lid body increases.

[0022] In addition, the toughness of the material affects the formability and opening properties of the cover. If the toughness of the material is low, forming cracks may occur in the edge groove (counter sink) and rivet part of the cover. In addition, when the internal pressure of the can increases unexpectedly, cracks will appear in the score part, resulting in an increased risk of leakage of the contents. In particular, these cracks are generated along the rolling direction. Therefore, toughness that can resist tensile stress and bending stress in the direction perpendicular to the rolling direction is required.

[0023] However, the method for manufacturing aluminum alloy plates for can covers having a composition close to that of the conventional 3104 aluminum alloy cannot solve the above two problems, namely, one or both of the strength (i.e., the compression resistance of the cover) and the toughness (i.e., the formability and opening property) of the material.

[0024] In order to solve the above problems, both high strength and high toughness can be achieved by performing a solution heat treatment in a continuous annealing furnace, for example, after hot rolling or during cold rolling. However, the material for can lids requires large-scale and low-cost production, and considering the environmental burden, it is required to reduce the energy consumption in the manufacturing process as much as possible. Therefore, it is preferable to manufacture without performing an intermediate heat treatment.

[0025] One aspect of the present disclosure preferably provides a method for producing an aluminum alloy plate for can ends, which can mix scrap raw materials derived from can materials and obtain an aluminum alloy plate for can ends that achieves both high strength and high toughness without performing intermediate heat treatment after hot rolling.

[0026] Solutions to the problem

[0027] One embodiment of the present disclosure relates to a method for manufacturing an aluminum alloy plate for can lids, comprising a step of casting an ingot, a step of homogenizing the ingot, and a step of rolling the ingot, wherein the ingot has a silicon Si content of 0.20 mass % to 0.47 mass %, an iron Fe content of 0.30 mass % to 0.59 mass %, a copper Cu content of 0.11 mass % to 0.40 mass %, a manganese Mn content of 0.70 mass % to 0.98 mass %, and a magnesium Mg content of 1.3 mass % to 3.7 mass %. In the rolling step, the ingot is hot-rolled and then cold-rolled without heat treatment.

[0028] According to the above structure, it is possible to mix the scrap raw materials from the can material, and to achieve high strength and high toughness of the aluminum alloy plate without performing a heat treatment process after hot rolling. In other words, a certain amount of scrap 3104 aluminum alloy for can bodies can be mixed, thereby reducing the use rate of new base metal and the emission of carbon dioxide. In addition, an aluminum alloy plate for can lids that can be used for positive pressure can lids that require high pressure resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a schematic diagram of the repeated bending test.

[0030] Figure 2 This is a flowchart of the method for producing an aluminum alloy plate according to the present embodiment.

[0031] Figure 3 It is a diagram showing S in the embodiment minGraph showing the relationship between the bending strength and the normalized number of repeated bendings. DETAILED DESCRIPTION

[0032] Embodiments to which the present disclosure is applied will be described below with reference to the accompanying drawings.

[0033] [1. First embodiment]

[0034] [1-1. Structure]

[0035] <Component>

[0036] The method for producing an aluminum alloy sheet for can lids disclosed herein (hereinafter also simply referred to as “alloy sheet”) contains aluminum (Al), silicon (Si), iron (Fe), copper (Cu), manganese (Mn), and magnesium (Mg).

[0037] The lower limit of the Si content is 0.20 mass %. The average value of the Si component specification of the 3104 aluminum alloy specified in JIS-H-4000:2014 is 0.30 mass %, and the average value of the Si component specification of the 5182 aluminum alloy specified in JIS-H-4000:2014 is 0.10 mass %. Therefore, by setting the Si content to 0.20 mass % or more, a large amount of 3104 aluminum alloy scrap can be mixed.

[0038] The upper limit of the content of Si is 0.47% by mass, preferably 0.30% by mass. If the content of Si exceeds 0.47% by mass, the difference between the solid solution temperature of Mg2Si and the solidus temperature of the aluminum matrix is ​​reduced, thereby making it difficult to dissolve Mg2Si in a large amount in the aluminum alloy ingot in the homogenization process. In addition, coarse Mg2Si will precipitate again during hot rolling. These all lead to reduced strength and toughness.

[0039] On the other hand, by setting the Si content to 0.30 mass % or less, Mg2Si can be relatively easily dissolved in the homogenization process. In addition, since the precipitation of coarse Mg2Si during hot rolling is suppressed, better strength and toughness can be obtained without heat treatment after hot rolling.

[0040] The lower limit of the Fe content is 0.30 mass %. The average value of the Fe component specification of the 3104 aluminum alloy is 0.40 mass %, and the average value of the Fe component specification of the 5182 aluminum alloy is 0.18 mass %. Therefore, by setting the Fe content to 0.30 mass % or more, a large amount of 3104 aluminum alloy scrap can be mixed.

[0041] The upper limit of the Fe content is 0.59% by mass, preferably 0.55% by mass. If the Fe content exceeds 0.59% by mass, abnormally coarse Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compounds (i.e., Giant Compounds) increase. As a result, crack propagation paths are generated, resulting in reduced toughness of the alloy plate. On the other hand, by setting the Fe content to less than 0.55% by mass, when the addition amount of Mg for supplementing strength and toughness is increased, the crystallization of the above-mentioned coarse intermetallic compounds can be suppressed.

[0042] The lower limit of the content of Cu is 0.11% by mass, preferably 0.17% by mass, and more preferably 0.20% by mass. If the content of Cu is less than 0.11% by mass, the Cu that increases the strength by solid solution or precipitation is insufficient, thereby causing the strength of the alloy plate to decrease. In addition, the average value of the Cu component specification of 3104 aluminum alloy is 0.15% by mass, and the average value of the Cu component specification of 5182 aluminum alloy is 0.075% by mass. Therefore, by setting the content of Cu to more than 0.11% by mass, a large amount of scrap of 3104 aluminum alloy can be mixed.

[0043] The upper limit of the content of Cu is 0.40 mass %, preferably 0.25 mass %. If the content of Cu exceeds 0.40 mass %, coarse precipitates increase and the toughness of the alloy plate decreases. In addition, by setting the content of Cu to below 0.25 mass %, it is possible to improve strength without significantly damaging toughness.

[0044] The lower limit of the content of Mn is 0.7% by mass. If the content of Mn is less than 0.7% by mass, the Mn that increases the strength by solid solution or precipitation is insufficient, resulting in a decrease in the average strength of the alloy plate. In addition, the average value of the Mn component specification of the 3104 aluminum alloy is 1.1% by mass, and the average value of the Mn component specification of the 5182 aluminum alloy is 0.35% by mass. Therefore, by setting the content of Mn to more than 0.7% by mass, a large amount of 3104 aluminum alloy scrap can be mixed.

[0045] The upper limit of the Mn content is 0.98% by mass. If the Mn content exceeds 0.98% by mass, abnormally coarse Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compounds increase. As a result, crack propagation paths are generated, resulting in reduced toughness of the alloy plate.

[0046] The lower limit of the content of Mg is 1.3% by mass, preferably 2.6% by mass. If the content of Mg is less than 1.3% by mass, insufficient Mg is added to increase the strength by solid solution, thereby reducing the average strength of the alloy plate. In addition, by setting the content of Mg to more than 2.6% by mass, better strength and toughness can be obtained without heat treatment after hot rolling.

[0047] The upper limit of the Mg content is 3.7% by mass. If the Mg content exceeds 3.7% by mass, the solidus temperature of the aluminum matrix decreases, and the solid solution temperature of Mg2Si increases, making it difficult to solid-dissolve the Mg2Si present in the ingot in the homogenization process. In addition, due to the decrease in the solidus temperature of the aluminum matrix, coarse Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compounds increase. Therefore, strength and toughness are impaired.

[0048] The alloy plate may contain titanium (Ti). The upper limit of the content of Ti is preferably 0.10 mass %. By containing Ti, the ingot structure of the alloy plate is refined. In addition, the alloy plate may contain zinc (Zn). The upper limit of the content of Zn is preferably 0.25 mass %. In addition, the alloy plate may contain chromium (Cr). The upper limit of the content of Cr is preferably 0.10 mass %.

[0049] The alloy plate may contain inevitable impurities within a range that does not significantly impair the performance of the alloy plate. That is, the alloy plate contains Si, Fe, Cu, Mn and Mg within the above ranges, respectively, and the remainder is composed of aluminum and inevitable impurities, or contains aluminum and inevitable impurities. The upper limit of the total amount of inevitable impurities is preferably 0.15% by mass. The remainder may contain substances other than aluminum and inevitable impurities.

[0050] <Material Strength and Compression Resistance>

[0051] According to experience, the compressive strength of the cover formed by the aluminum alloy plate has a strong positive correlation with the value V of the following mathematical formula (1), where the value V is determined by the material strength of the aluminum alloy plate, that is, the 0.2% yield strength σ 0.2 , tensile strength σ B , the average value of 0.2% yield strength and tensile strength σ fm , and plate thickness t (refer to Sumitomo Light Metals Technical Report, Vol. 54, No. 1, 2013, pp. 185-195).

[0052] V=t 2.27 ×σ fm / (σ 0.2 / σ B ) (1)

[0053] Therefore, in the cover body formed of the aluminum alloy plate, the greater the plate thickness, the higher the pressure resistance. Since the aluminum alloy plate of the present disclosure has a high material strength, it is possible to suppress the increase in plate thickness in order to improve the pressure resistance.

[0054] In addition, the larger the S calculated by the following mathematical formula (2), the greater the compressive resistance of the cover. In particular, considering the anisotropy of the material, it is preferred that the minimum value S of the three Ss obtained from the measurement results of the tensile tests in the 0° direction, 45° direction, and 90° direction relative to the rolling direction is min Larger.

[0055] S=σ fm / (σ 0.2 / σ B ) (2)

[0056] S min It is preferably 330 MPa or more, and more preferably 350 MPa or more. min By setting the thickness to the above value, it is possible to form a cover body having a sufficient pressure resistance value without significantly increasing the plate thickness.

[0057] The 0.2% yield strength σ in equations (1) and (2) 0.2 and tensile strength σ B The measurement is performed by the method specified in JIS-Z-2241: 2011. For example, a micrometer is used to measure the plate thickness t.

[0058] <Toughness>

[0059] It is known that the toughness of the aluminum alloy plate affects the formability of the cover body and the force required to open the opening of the score portion (ie, the opening force).

[0060] (Number of repeated bending)

[0061] One of the evaluation indexes of the toughness of aluminum alloy plates is the repeated bending test. If the plate thickness is the same, the more repeated bending times, the better the toughness of the aluminum alloy plate. Since cracks along the rolling direction are particularly a problem for aluminum alloy plates, the number of repeated bending times when the rolling direction is parallel to the bending ridge direction is important. The aluminum alloy plate disclosed in the present invention can achieve a good number of repeated bending times.

[0062] The repeated bending test is carried out according to the following steps. Figure 1 As shown, a strip-shaped test piece with a width of 12.5 mm and a length of 200 mm was arranged so that the direction of the bending ridgeline R was parallel to the rolling direction D of the alloy plate. Both ends of the test piece were fixed with chucks, and a tensile force of 200 N was applied.

[0063] In this state, a clamp with a bending radius R of 2.0 mm, which is arranged at a position 150 mm away from the end of the specimen fixed on a fixed chuck on one side along the length direction of the specimen, is used as a fulcrum. The chuck on the other side is rotated 90° to the left and right, and the bending is repeated, and the number of bends until the specimen breaks is measured.

[0064] The number of bends is counted as one operation of bending 90° to the left or right and returning to the original position. If the specimen breaks during the process, the angle θ (0°-90°) is read and the number of repeated bends N is calculated using the following mathematical formula (3). In mathematical formula (3), N0 is the total number of operations of bending 90° to the left or right and returning from the position bent to 90° to the original 0° position until the specimen breaks.

[0065] N=N0+θ / 90 (3)

[0066] In the repeated bending evaluation, the larger the plate thickness, the more disadvantageous it is, so it is necessary to use the reference plate thickness for correction. Therefore, taking the plate thickness of 0.235 mm as the reference, the standardized repeated bending number N is calculated by the following mathematical formula (4): s . t (mm) is the plate thickness of the specimen.

[0067] N s =N×t / 0.235 (4)

[0068] The normalized repeated bending number of the aluminum alloy plate of the present disclosure is preferably 17 or more, more preferably 18 or more. By setting the normalized repeated bending number to the above number, the toughness of the aluminum alloy plate is improved, and sufficient formability of the cover can be obtained.

[0069] (Second phase particles)

[0070] Toughness is affected by strength and the distribution of second-phase particles. That is, the greater the strength and the higher the density of second-phase particles, the lower the toughness. In particular, if the content of Mg and Si increases, Mg2Si particles are easily formed. As a result, Mg2Si particles become the starting point and expansion path of cracks, resulting in a decrease in toughness.

[0071] The aluminum alloy plate disclosed herein has an area of ​​0.3 μm in the center region of the plate thickness direction of the cross section perpendicular to the plate surface and parallel to the rolling direction. 2 The ratio of the above Mg2Si particles to the total area of ​​the central region is preferably 0.2% or less, more preferably 0.1% or less.

[0072] For example, the area ratio of Mg2Si particles can be measured by the following method: Among the surfaces of the measurement sample, the surface to be measured (ie, the cross section perpendicular to the plate surface of the alloy plate, ie, the rolling surface and parallel to the rolling direction) is mechanically polished to a mirror finish.

[0073] The polished surface (i.e., the cross section perpendicular to the plate surface, i.e., the rolling surface, of the alloy plate and parallel to the rolling direction) was observed using a scanning electron microscope (SEM) to obtain 10 fields of view. The acceleration voltage of the SEM was set to 15 kV, the magnification was set to 1000 times, and the range of one field of view was set to 0.012 mm. 2 To take pictures, the reflected electron component image (COMPO) is obtained.

[0074] The COMPO images were analyzed using the image analysis software ImageJ. Specifically, the brightness value that appeared most frequently among the 256 color levels in the image was set as the background brightness, and particles with a brightness lower than the value obtained by subtracting 30 from the brightness value that appeared most frequently were determined to be Mg2Si particles.

[0075] The calculated area of ​​the Mg2Si particles identified is 0.3 μm 2 The total area of ​​the above particles is divided by the imaging area of ​​10 fields of view to calculate the area as 0.3 μm 2 The above is the ratio of the total area of ​​Mg2Si particles in the cross section.

[0076] <Method for Manufacturing Aluminum Alloy Plate>

[0077] The aluminum alloy plate of the present disclosure is obtained by the method for manufacturing the aluminum alloy plate of the present disclosure. Figure 2 As shown, the method for manufacturing an aluminum alloy plate of the present disclosure includes a casting step S110 , a homogenization step S120 , a rolling step S130 , and a coating step S140 .

[0078] (Casting process)

[0079] In this process, a semi-continuous casting method (i.e., DC casting) is performed on an aluminum alloy having the components of the aluminum alloy plate disclosed in the present invention to produce an ingot according to a conventional method. At this time, an Al-Ti-B-based micronizing material may also be added to the substrate. Thus, the coarsening of the grains and the second phase particles of the ingot can be suppressed.

[0080] (Homogenization process)

[0081] In this process, after the surface of the ingot is face-cut, the ingot is placed in a soaking furnace for homogenization treatment. The temperature of the homogenization treatment is preferably above the solid solution temperature of Mg2Si and below the solidus temperature of the aluminum matrix.

[0082] When the temperature of the homogenization treatment is above the solid solution temperature of Mg2Si, the amount of the second phase particles, i.e., Mg2Si, crystallized and precipitated in the ingot can be reduced. As a result, the strength and toughness of the aluminum alloy plate are improved. In addition, the homogenization treatment temperature is preferably 40°C or higher than the solid solution temperature of Mg2Si. Thus, the amount of Mg2Si can be greatly reduced.

[0083] In addition, by setting the homogenization treatment temperature to below the solidus temperature of the aluminum matrix, the aluminum alloy sheet can be manufactured without causing local melting. In addition, the homogenization treatment temperature is preferably 10°C or more lower than the solidus temperature of the aluminum matrix. Thus, the aluminum alloy sheet can be stably produced without causing local melting.

[0084] The solid solution temperature of Mg2Si and the solidus temperature of the aluminum matrix are uniquely determined by the composition of the aluminum alloy. For example, the phase equilibrium diagram can be calculated by inputting the composition of the aluminum alloy into the thermodynamic calculation software "JMatPro" developed by Sente Software, thereby calculating the solid solution temperature of Mg2Si and the solidus temperature of the aluminum matrix. The phase diagram calculation (CALPHAD) method is used as a thermodynamic model for calculating the phase equilibrium diagram.

[0085] The time of the homogenization treatment is preferably, for example, more than 1 hour and less than 20 hours. When the time of the homogenization treatment is more than 1 hour, the temperature of the entire slab becomes uniform, the segregation of the ingot structure is easily eliminated, and the Mg2Si particles are easily dissolved again. The longer the homogenization treatment time is, the more Mg2Si particles can be dissolved again. However, when the homogenization treatment time exceeds 20 hours, the effect of the homogenization treatment becomes saturated.

[0086] (Rolling process)

[0087] In this process, the homogenized ingot is rolled. This process includes a hot rolling process S131 and a cold rolling process S132.

[0088] The hot rolling process S131 includes a rough rolling process and a finishing rolling process. In the rough rolling process, the ingot is processed into a plate having a thickness of about tens of mm by reversible rolling. In the finishing rolling process, the thickness of the plate is reduced to about several mm by, for example, tandem rolling, and the plate is wound into a coil to form a hot rolled coil.

[0089] When the total reduction rate of the finishing rolling is high, the aluminum alloy sheet forms a recrystallized structure after coiling, thereby increasing the aggregation of the cube orientation. When the coiling temperature of the finishing rolling is high, the aluminum alloy sheet forms a recrystallized structure after coiling, thereby increasing the aggregation of the cube orientation. By increasing the aggregation of the cube orientation of the aluminum alloy sheet, the number of repeated bending can be increased.

[0090] The cold rolling step S132 is performed after the hot rolling step S131. In the cold rolling, the hot rolled coil is rolled until the product plate thickness is reached. The cold rolling can be a single-stand rolling or a continuous rolling mill rolling. In the single-stand cold rolling, the rolling is preferably performed in multiple passes of two or more.

[0091] The cold rolling rate (i.e., the target total reduction rate) is preferably 70% or more, more preferably 80% or more. By setting the lower limit of the cold rolling rate to the above value, the strength of the aluminum alloy plate can be improved. On the other hand, the cold rolling rate is preferably 90% or less. By setting the upper limit of the cold rolling rate to the above value, the anisotropy of the grain structure is reduced, and the toughness against the tensile stress and bending stress in the direction perpendicular to the rolling direction is improved.

[0092] The cold rolling ratio R (%) was calculated by the following mathematical formula (5) using the plate thickness t0 (mm) of the hot-rolled plate and the plate thickness t1 (mm) of the product after cold rolling.

[0093] R=(t0-t1) / t0×100 (5)

[0094] In the rolling process S130, after the ingot is hot rolled, the cold rolling is completed without heat treatment (i.e., annealing). That is, in the manufacturing method of the aluminum alloy plate disclosed in the present invention, the plate (i.e., coil) does not need to be heat treated between hot rolling and cold rolling or in the cold rolling process, and the cold rolling can be performed until the thickness of the final product is reached. In this way, the number of processes can be greatly reduced, the production efficiency can be improved, and the energy consumption can be reduced.

[0095] (Painting process)

[0096] In this process, the plate obtained by cold rolling the ingot is coated and baked. Specifically, the coil that has been cold rolled to the product plate thickness is first pre-coated on a coating line or the like. The surface of the cold rolled coil is degreased, cleaned, and chemically converted, and then the coating is applied and then the coating is baked.

[0097] In the chemical conversion treatment, chemical solutions such as chromate and zirconium are used. Epoxy and polyester are used as coatings. The above chemical solutions and coatings can be selected according to the application. In the coating baking treatment, the coil is heated at a physical temperature (PMT: Peak Metal Temperature) of 220°C or more for about 30 seconds.

[0098] At this time, the lower the PMT, the more the recovery of the material is suppressed, so that the strength of the alloy plate can be highly maintained. Therefore, the baking temperature (i.e., PMT) of the coating is preferably below 270°C. In addition, in order to improve toughness, the cold rolling rate can be reduced, and the resulting strength reduction can be compensated by lowering the PMT.

[0099] [1-2. Effect]

[0100] According to the embodiments described in detail above, the following effects can be obtained.

[0101] (1a) It is possible to mix scrap raw materials from can materials and simultaneously achieve high strength and high toughness of the aluminum alloy plate. In other words, a certain amount of scrap 3104 aluminum alloy for can bodies can be mixed into the raw materials, thereby reducing the use rate of new base metal and the emission of carbon dioxide. In addition, it is possible to obtain an aluminum alloy plate for can lids that can be used for positive pressure can lids that require high pressure resistance.

[0102] [2. Other embodiments]

[0103] The embodiments of the present disclosure have been described above, but the present disclosure is not limited to the above embodiments, and various embodiments can be adopted.

[0104] (2a) In addition to the method for producing an aluminum alloy plate of the above-described embodiment, the present disclosure also includes various forms such as an aluminum alloy plate obtained by the production method and a component composed of the aluminum alloy plate.

[0105] (2b) The functions of one component in each of the above-mentioned embodiments may be shared by multiple components, or the functions of multiple components may be integrated into one component. In addition, part of the components of the above-mentioned embodiments may be omitted. At least part of the components of each of the above-mentioned embodiments may be added to the components of the other embodiments, or at least part of the components of each of the above-mentioned embodiments may be replaced with the components of the other embodiments, etc. In addition, all the methods included in the technical ideas determined by the sentences recorded in the claims are embodiments of the present disclosure.

[0106] [3. Example]

[0107] Hereinafter, the contents of the test performed to confirm the effect of the present disclosure and the evaluation thereof will be described.

[0108] <Manufacturing of aluminum alloy sheets>

[0109] As examples and comparative examples, aluminum alloy plates of S1 to S12 shown in Tables 1 and 2 were produced. The specific production steps are described below.

[0110] First, an ingot containing the components (mass %) of alloy numbers 1 to 7 shown in Table 3, with the remainder consisting of aluminum and inevitable impurities, was manufactured by a semi-continuous casting method. The ingot contained 0.10 mass % or less of Ti, 0.25 mass % or less of Zn, 0.10 mass % or less of Cr, and 0.15 mass % or less of inevitable impurities.

[0111] Next, the six surfaces of the ingot are face cut. After that, the ingot is placed in a furnace and subjected to a homogenization treatment. The temperature of the homogenization treatment is shown in Table 1. For ingots S1 to S11, the temperature of the homogenization treatment is set to be above the solid solution temperature of Mg2Si shown in Table 3 and below the solidus temperature of the aluminum matrix. For the S12 ingot, the temperature of the homogenization treatment is set to be lower than the solid solution temperature of Mg2Si shown in Table 3. After more than four hours of homogenization treatment, the ingot is taken out of the furnace, hot rolling is immediately started, and a rolled plate is formed.

[0112] The hot-rolled rolled sheet was cold-rolled. The target total reduction ratio during cold rolling is shown in Table 1. The product sheet thickness after cold rolling (ie, t1 in the mathematical formula (5)) was approximately in the range of 0.235±0.01 mm.

[0113] After cold rolling, a coating baking treatment was performed for 30 seconds. The physical temperature (PMT) during coating baking is shown in Table 1. Through the above steps, aluminum alloy plates S1 to S12 were obtained. In addition, Table 1 also shows the plate thickness (i.e., product plate thickness) of the aluminum alloy plates S1 to S12 measured using a micrometer.

[0114] [Table 1]

[0115]

[0116] [Table 2]

[0117]

[0118] [Table 3]

[0119]

[0120] <Evaluation of aluminum alloy sheet>

[0121] (Tensile properties)

[0122] Three No. 5 test pieces specified in JIS-Z-2241: 2011 were prepared from aluminum alloy sheets S1 to S12, respectively. The longitudinal directions of the three test pieces extended in directions forming angles of 0°, 45°, and 90° with respect to the rolling direction, respectively.

[0123] The above test pieces were subjected to a tensile test in accordance with JIS-Z-2241:2011 to measure the 0.2% yield strength and tensile strength. Tables 1 and 2 show the 0.2% yield strength σ 0.2 and tensile strength σ B The measurement results, as well as the average values ​​of 0.2% yield strength and tensile strength σ fmIn addition, three S are calculated based on the measurement results of the tensile tests in the 0° direction, 45° direction, and 90° direction and mathematical formula (2). The minimum value S of these S is min As shown in Table 2.

[0124] (toughness)

[0125] For the aluminum alloy sheets S1 to S12, the measurement method described in the embodiment was used to measure the area of ​​0.3 μm. 2 The ratio of the total area of ​​the above Mg2Si particles in the cross section (area ratio) was calculated. The measurement results are shown in Table 2.

[0126] For the aluminum alloy sheets S1 to S12, the number of repeated bending and the normalized number of repeated bending were calculated according to the measurement method described in the embodiment and mathematical formulas (3) and (4). The results are shown in Table 2.

[0127] (Waste mixing ratio)

[0128] Regarding the composition of the aluminum alloy plates S1 to S12, it was determined whether the possible mixing ratio of the scrap of the 3104 aluminum alloy was 50% by mass or more. In addition, the possible mixing ratio of the scrap of the 3104 aluminum alloy was determined based on Table 4.

[0129] Table 4 shows the correspondence between the mixing ratio of the 3104 aluminum alloy and the 5182 aluminum alloy and the average value of the component specifications. The first row of Table 4 is the average value of the component specifications of the 3104 aluminum alloy, and the second row is the average value of the component specifications of the 5182 aluminum alloy.

[0130] For example, when the mixing ratio of 3104 aluminum alloy is 50 mass %, the average value of Si is 0.20 mass %, the average value of Fe is 0.29 mass %, the average value of Cu is 0.11 mass %, the average value of Mn is 0.7 mass %, and the average value of Mg is 2.8 mass %.

[0131] Therefore, when the ratio of each component in the aluminum alloy plate is equal to or higher than the above-mentioned values ​​of Si, Fe, Cu, Mn, and Mg, the possible mixing ratio of the 3104 aluminum alloy plate is 50% by mass or more. The higher the mixing ratio of the 3104 aluminum alloy, the more the content of Si, Fe, Cu, and Mn increases, and the more the content of Mg decreases. The aluminum alloy plates S2-S12 can be mixed with more than 50% by mass of scrap 3104 aluminum alloy.

[0132] [Table 4]

[0133]

[0134] (evaluate)

[0135] Figure 3The S of each of the aluminum alloy plates S1-S12 is shown. min The relationship between the normalized number of repeated bends. Figure 3 In the figure shown, S min The larger the value and the normalized number of repeated bending times are (that is, the more the point (plot) is located in the upper right of the graph), the better the characteristics are.

[0136] The aluminum alloy sheet S1 has a low Mg content and therefore cannot obtain sufficient strength (i.e., S min ). In this regard, the aluminum alloy plates S2-S12 obtained by the manufacturing method disclosed in the present invention all have an S of 330 MPa or more. min and more than 17 standardized repeated bending times.

[0137] In addition, the S8-S11 aluminum alloy sheet with high Mg content min All of them are above 350MPa. In particular, the Si content of aluminum alloy plates S10 and S11 is lower than that of S8 and S9, so although the Mg content is high, the area ratio of Mg2Si particles is less than 0.1%, and both strength and toughness are excellent. On the other hand, in S12, the homogenization temperature is lower than the solid solution temperature of Mg2Si, so the area ratio of Mg2Si particles becomes larger, and although the Mg content is high, the S min and the number of standardized repeated bendings is relatively small.

[0138] For all aluminum alloys, the lower the paint baking temperature (PMT), the higher the strength (i.e., S min For example, when comparing aluminum alloy plates S2 and S3, S4 and S5, S6 and S7, S8 and S9, and S10 and S11, it is found that the embodiment with a lower coating baking temperature has a higher S min On the other hand, the higher the coating baking temperature of the examples, the greater the number of standardized repeated bending times.

Claims

1. A method for manufacturing an aluminum alloy plate for a can cover, characterized in that: Including the following processes: The process of casting an ingot, in which: The content of silicon Si is 0.20 mass % or more and 0.47 mass % or less, The content of iron Fe is 0.30 mass % or more and 0.59 mass % or less, The content of copper Cu is 0.11 mass % or more and 0.40 mass % or less, The content of manganese Mn is 0.70 mass % or more and 0.98 mass % or less, The content of magnesium Mg is 1.3 mass % or more and 3.7 mass % or less, and The remainder consists of aluminum Al and inevitable impurities, or contains the aluminum and the inevitable impurities; A step of homogenizing the ingot; as well as The process of rolling the homogenized ingot, In the rolling step, the ingot is hot rolled and then cold rolled without heat treatment.

2. The method for manufacturing an aluminum alloy plate for can covers according to claim 1, characterized in that: In the homogenization step, the ingot is homogenized at a temperature above the solid solution temperature of Mg2Si and below the solidus temperature of the aluminum matrix.

3. The method for manufacturing an aluminum alloy plate for can covers according to claim 2, characterized in that: In the casting process, the following ingot is cast, wherein: The content of silicon Si is 0.20 mass % or more and 0.47 mass % or less, The content of iron Fe is 0.30 mass % or more and 0.55 mass % or less, The content of copper Cu is 0.17 mass % or more and 0.25 mass % or less, The content of manganese Mn is 0.70 mass % or more and 0.98 mass % or less, The content of magnesium Mg is 2.6 mass % or more and 3.7 mass % or less, and The remainder consists of aluminum Al and inevitable impurities, or contains the aluminum and the inevitable impurities.

4. The method for manufacturing an aluminum alloy plate for can covers according to claim 3, characterized in that: In the casting process, the following ingot is cast, wherein: The content of silicon Si is 0.20 mass % or more and 0.30 mass % or less, The content of iron Fe is 0.30 mass % or more and 0.55 mass % or less, The content of copper Cu is 0.17 mass % or more and 0.25 mass % or less, The content of manganese Mn is 0.70 mass % or more and 0.98 mass % or less, The content of magnesium Mg is 2.6 mass % or more and 3.7 mass % or less, and The remainder consists of aluminum Al and inevitable impurities, or contains the aluminum and the inevitable impurities.

5. The method for manufacturing an aluminum alloy plate for can covers according to claim 4, characterized in that: The method further includes a coating baking step in which a plate obtained by cold rolling the ingot is baked and coated at a temperature below 270°C.

6. The method for manufacturing an aluminum alloy plate for can covers according to claim 5, characterized in that: In the rolling process, cold rolling is performed at a reduction ratio of 90% or less.

Citation Information

Patent Citations

  • Aluminum alloy laminate for can cover adapted to recycling and manufacture thereof

    JP1997070925A

  • Aluminum alloy-laminated sheet and its production

    JP1999269594A

  • Aluminum alloy sheet for can end

    JP2000160273A

  • Manufacture of aluminum alloy hard sheet for can-top

    JP2001073106A

  • Aluminum alloy sheet for negative pressure can-top

    JP2016160511A